2014
DOI: 10.5294/edu.2014.17.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the National Bilingual Program in Colombia: An Interim Assessment

Abstract: Implementación del Programa Nacional de Bilingüismo en Colombia: un balance intermedio 1 ResumenEl Programa Nacional de Bilingüismo colombiano busca mejorar el aprendizaje del inglés como lengua extranjera en los distintos niveles de la enseñanza. Hasta ahora se han realizado pocos estudios sistemáticos dentro de las escuelas que permitan conocer el estado real en que se encuentran en relación con ese Programa. En nuestra investigación, realizada en la ciudad de Santiago de Cali, se utilizaron encuestas, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
1
4
0
14
Order By: Relevance
“…The need to expand the current coverage is quite evident for the primary and preschool levels where the compulsory nature of teaching English has been imposed in the framework of the National Bilingual Program. (p. 192) 6 Similar findings have been demonstrated in other studies (Cárdenas & Miranda, 2014;Cárdenas, González, & Álvarez, 2010;Correa & González, 2016;González, 2007). Therefore, while taking into account the previous concerns, providing 6 Translation by the authors.…”
Section: Professional Developmentsupporting
confidence: 82%
See 1 more Smart Citation
“…The need to expand the current coverage is quite evident for the primary and preschool levels where the compulsory nature of teaching English has been imposed in the framework of the National Bilingual Program. (p. 192) 6 Similar findings have been demonstrated in other studies (Cárdenas & Miranda, 2014;Cárdenas, González, & Álvarez, 2010;Correa & González, 2016;González, 2007). Therefore, while taking into account the previous concerns, providing 6 Translation by the authors.…”
Section: Professional Developmentsupporting
confidence: 82%
“…In Colombia there have been proposals to support teachers professionally, but taking into account some of the analysis of those initiatives, there is still a lack of complete satisfaction due to several factors such as time, range, coverage and follow up to the results of those programs. For example, recent studies on professional development for language teachers in elementary schools in Colombia show that even though the Ministry of Education through the National Bilingual Program has made several efforts to reach the bilingual goals proposed for the year 2019, they have not yet been achieved and there are still many aspects of this program that require attention (Álvarez et al, 2015;Cárdenas & Miranda, 2014;Cárdenas, González, & Álvarez, 2010;Correa & González, 2016;González, 2007;McNulty & Quinchía, 2007). One of these aspects has to do with teachers' qualifications.…”
Section: Professional Developmentmentioning
confidence: 99%
“…La obligatoriedad de la enseñanza del inglés como segunda lengua, de acuerdo a (Cardenas & Miranda, 2014), está presente en los currículos de la mayoría de los países de diferentes latitudes de manera incuestionable, si se toma en consideración a Latinoamérica, esta materia está presente en todos los niveles, en el caso concreto del La aplicación de esta técnica tuvo un éxito relativo al tratar de dinamizar la clase, para no caer en el aburrimiento, propiciando que se convierta en un lugar de participación colaborativa, a través de ciertas rutinas que ayudan a desarrollar la expresión oral en inglés, se vuelve muy interactiva, con la participación de todos los estudiantes, se puede tratar temas específicos con comunicación fluida, y practicando el vocabulario, reconocimiento de palabras nuevas y estructuración correcta de las frases.…”
Section: Referencial Teóricounclassified
“…Colombia launched the Programa Nacional de Bilingüismo (National Bilingual Program) in 2004, whose goal was to ensure that students finish high school reaching CEFR level B1 in English by 2019 (Correa & González, 2016), with a focus on boosting the students' communicative competencies in English, so that they can help the country in the economic and cultural fields (Cárdenas & Miranda, 2014). Nevertheless, the 2011 Colombian National English test showed that 90% of high school students who took the exam for the first time barely achieved level A1 upon graduation, whereas only 2% surpassed level B1 (Sánchez-Jabba, 2013).…”
Section: Chile Introduced the Programa Inglés Abre Puertas (Piap Engmentioning
confidence: 99%